2020
DOI: 10.1093/nsr/nwaa086
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolomic and lipidomic alterations associated with COVID-19

Abstract: The pandemic of the coronavirus disease 2019 has become a global public health crisis. The symptoms of COVID-19 range from mild to severe conditions. However, the physiological changes associated with COVID-19 are barely understood. In this study, we performed targeted metabolomic and lipidomic analyses of plasma from a cohort of COVID-19 patients who had experienced different symptoms. We found the metabolite and lipid alterations exhibit apparent correlation with the course of disease in these COVID-19 pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
309
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(360 citation statements)
references
References 23 publications
26
309
1
2
Order By: Relevance
“…Previous studies have reported that lipid metabolism impairment may be involved in the pathogenesis of sepsis secondary to pneumonia and in uenza [8][9][10]. Similarly, recent studies observed dyslipidemia in patients infected with SARS-CoV-2, using MS analysis [6,7] and routine laboratory lipid tests [11], indicating that blood lipid might involve in the pathogenesis of COVID-19. In the study of Wei et al [11], a serum hypolipidemia was found in the COVID-19 patients, which showed that the serum level of TC, HDL-C and LDL-C in the patients with COVID-19 were signi cantly lower than healthy subjects, especially in the severe and critical cases.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have reported that lipid metabolism impairment may be involved in the pathogenesis of sepsis secondary to pneumonia and in uenza [8][9][10]. Similarly, recent studies observed dyslipidemia in patients infected with SARS-CoV-2, using MS analysis [6,7] and routine laboratory lipid tests [11], indicating that blood lipid might involve in the pathogenesis of COVID-19. In the study of Wei et al [11], a serum hypolipidemia was found in the COVID-19 patients, which showed that the serum level of TC, HDL-C and LDL-C in the patients with COVID-19 were signi cantly lower than healthy subjects, especially in the severe and critical cases.…”
Section: Discussionmentioning
confidence: 91%
“…Consequently, some clinical characteristics, the in ammation index and cytokine levels have been used as indictors to re ect the severity of COVID-19 by us and others [4,5]. Recently, emerging evidence suggested that lipid metabolism dysregulation might promote the progression of COVID-19 as revealed by mass spectrometry (MS)-based proteomics analysis [6,7]. Although MS analysis is not commonly performed, blood lipid is routinely examined using automatic biochemical instruments in clinical laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical medicine, serum albumin can be measured via standard serum laboratory testing that measures both free and bound albumin. Free fatty Acids (FFA), melatonin (2,(48)(49)(50) and the SARS-CoV-2 virions are transported bound to albumin as are glycolates. Studies on drug interactions confirm both competitive and non-competitive binding (49,(51)(52)(53)(54).…”
Section: Human Serum Albuminmentioning
confidence: 99%
“…Previous studies have reported that lipid metabolism impairment may be involved in the pathogenesis of sepsis secondary to pneumonia and in uenza [9][10][11]. Similarly, recent studies observed dyslipidaemia in patients infected with SARS-CoV-2, especially in the severe cases, using MS analysis, [6][7][8], indicating that blood lipids might serve as a marker of COVID-19 severity. Among the altered lipids, ApoA1 was signi cantly decreased.…”
Section: Discussionmentioning
confidence: 87%
“…Consequently, some clinical characteristics, the in ammation index and cytokine levels have been used as indictors to re ect the severity of COVID-19 by us and others [4,5]. Recently, emerging evidence suggested that lipid metabolism dysregulation might promote the progression of COVID-19 as revealed by mass spectrometry (MS)-based proteomics analysis [6][7][8]. Although MS analysis is not commonly performed, blood lipids are routinely examined using automatic biochemical instruments in clinical laboratories.…”
Section: Introductionmentioning
confidence: 99%